Keanekaragaman Subordo Serpentes Di Kawasan Pantai Sendangbiru Kabupaten Malang Provinsi Jawa Timur - Syauqi Abdillah (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2023)
The diversity of the Suborder Serpentes has an important role in the ecosystem and is used as a parameter of environmental quality. The high diversity of the Suborder Serpentes in Indonesia is not matched by adequate research and publications. The Sendangbiru beach area is a Nature Reserve area which has the potential to become a natural habitat for all types of animals, especially the Serpentes Suborder because it has a stable temperature and many unspoiled habitats. This study aims to find out what types of snakes are in the area and how the diversity, level of abundance, and dominance of the Suborder Serpentes are. This research method uses a descriptive explorative method by exploring the routes on Sendangbiru beach area. The suborder Serpentes found will be measured for morphometry, namely by measuring the snake's body which includes body length, tail length, total length, number of scales, and sex. This study found 6 species of snakes. The six species found consisted of the Aglypha, Solenoglypha, and Ophistoglypha snakes. The snake species that have been found belong to the Colubridae family as many as 4 species from 3 different genera, namely the species Dendrelaphis pictus of the genus Dendrelaphis, the species Ahaetulla nasuta and Ahaetulla prasina of the genus Ahaetulla, and the species Chrysopelea paradisi of the genus Chrysopelea. While the other 2 species are the Viperidae family with the species name Cryptelytrops albolabris, the genus Cryptelytrops, and the Pythonidae family, with the species name Malayopython reticulatus, the genus Malayopython. The diversity index (H') in the Sendangbiru beach area is 1.79 with a moderate diversity value, an evenness value (E) 1 and indicates that the suborder found on Sendangbiru beach area has an even value and stable community, and a dominance value (C ) 0.17 with a low dominance value.